Effect of Depression in The Elderly on Glaucoma and Pharmacotherapy Options - Syaiful Anwar; Yulia Fatima Bessing; Erikavitri Yulianti (Jurnal Psikiatri Surabaya)
Introduction: Depression in the elderly is often not detected because elderly people who are depressed show more somatic or cognitive complaints than affective complaints. The relationship between depression and the progression of glaucoma has been studied and taken into consideration in the selection of therapy to be given. Methods: This report is a case report from a patient who has been given an explanation and received consent regarding a psychiatric interview, physical examination and support, interventions, case discussion presentations, and the confidentiality of all patient personal information. Case: Education was carried out on a 72-year-old patient with a Major Depressive Episode without psychotic symptoms who also had glaucoma a few months after complaining of depression. The education provided includes knowledge about depression and its relationship to glaucoma, a management plan in the form of advice for hospitalization in a hospital that has a psychiatrist and an ophthalmologist. Conclusion: Depression in the elderly can affect the progression of glaucoma. The choice of psychopharmacological therapy needs to be adjusted by considering its side effects on the possibility of glaucoma or the risk of aggravating the progression of glaucoma.